Annual World Bank Conference on Development Economics 2007, Global : Rethinking Infrastructure for Development (Annual World Bank Conference on Development Economics., 2007)
This book provides profiles of over 50 countries with 54 development indicators about people, environment, economy, technology, infrastructure, trade and finance, all in one handy, pocketsized volume. A must have for anyone interested in today's development challenges in subSaharan Africa.